Starość w starożytnej literaturze ormiańskiej - Żelazny, Jan W. (Vox Patrum, 2011)
In Armenian tradition, old age, with its grey hair, symbolizes wisdom and responsibility. The country’s tradition depends on elderly people. Opinions expressed in the Armenian literature of that time are similar to the ones regarding the same issue occurring in the entire Middle East. Only two issues arising interest and cause surprise. The first thought concerns the gossiping of elderly women, which does not mean anything wrong, but may rather be related to method of transferring tradition that creates collective memory of a nation. The second question is close relation between old age and adolescence. Both children and elderly people are the basic groups in the community on whose survival the nation’s future depends.